Palaeoenvironmental evidence for woodland conservation in Northern Iceland from settlement to the twentieth century. (3rd July 2018) - Tisdall, Eileen; Barclay, Rebecca; Nichol, Amy; McCulloch, Robert; Simpson, Ian; Smith, Huw; Vésteinsson, Orri
ABSTRACT: Narratives of Norse arrival in Iceland highlight the onset of land degradation and loss of woodland cover as major and long-term environmental consequences of settlement. However, deliberate and sustained land resource management in Iceland is increasingly being recognised, and in this paper we assess whether woodland areas were deliberately managed as fuel resources. Our study location is the high status farm site at Hofstaðir in northern Iceland. A palynological record was obtained from a small basin located just inside the farm boundary wall and the geoarchaeological record of fuel use obtained from waste midden deposits associated with the farm. Both environmental records are temporally constrained by tephrochronology and archaeological records. When viewed within the broader landscape setting, our findings suggest that there was near continuous use of birch wood from early settlement to the present day, that it was actively conserved throughout the occupation of the site and that there were clear distinctions in fuel resource utilisation for domestic and more industrial purposes. Our analyses open discussion on the role of local woodlands and their management in the Norse farm economy.